2010
DOI: 10.1016/j.amepre.2009.08.027
|View full text |Cite
|
Sign up to set email alerts
|

Racial Disparities in Age at Preventable Hospitalization Among U.S. Adults

Abstract: Background-Similar to the well-documented racial inequities in health status, disease burden, healthcare access, and hospitalization, studies have generally found higher rates of hospitalization due to ambulatory care-sensitive conditions for blacks compared to whites. Beyond identifying disparity in rates of disease or risks of hospitalization, identifying disparity in age at hospitalization may provide deeper insight into the social and economic consequences of disparities on individuals, families, and commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 26 publications
2
37
0
2
Order By: Relevance
“…De outra parte, estudos americanos revelam que, para categorias étnicas socialmente excluídas, é mais difícil o acesso aos serviços básicos de saúde, e, com isso, há carência de ações de prevenção, falta de diagnóstico e tratamento precoce, o que acarreta complicações das doenças e aumento das internações sensíveis 24,25 .…”
Section: Discussionunclassified
“…De outra parte, estudos americanos revelam que, para categorias étnicas socialmente excluídas, é mais difícil o acesso aos serviços básicos de saúde, e, com isso, há carência de ações de prevenção, falta de diagnóstico e tratamento precoce, o que acarreta complicações das doenças e aumento das internações sensíveis 24,25 .…”
Section: Discussionunclassified
“…Race is associated with disparate clinical outcomes in multiple health conditions (1). Such disparities are particularly conspicuous in diabetes, where racial minorities have higher rates of microvascular complications and mortality (2).…”
Section: Introductionmentioning
confidence: 99%
“…Such disparities are particularly conspicuous in diabetes, where racial minorities have higher rates of microvascular complications and mortality (2). Compared to other racial groups, blacks with diabetes make more frequent emergency department visits for hyperglycemia and hypoglycemia (35), are hospitalized at younger ages (1), have higher readmission rates(6), and experience more preventable complications (2). Among the complications of diabetes, the racial gap in disease incidence is widest in nephropathy; blacks are nearly four times more likely to progress to end-stage renal disease compared to their white counterparts(2).…”
Section: Introductionmentioning
confidence: 99%
“…9 Recent studies have identified that psychosocial factors such as race, socioeconomic status and mental disorders may increase the risk of hospitalizations for ACSCs. 7,[10][11][12][13] Of the potential psychosocial risk factors for hospitalizations for ACSCs identified, mental disorders represent an area that could be amenable to intervention, and thus may reduce the number and cost of potentially preventable hospitalizations.…”
Section: Introductionmentioning
confidence: 99%